CHEMICAL COMPOSITION AND ANTIBACTERIAL AND ANTIOXIDANT ACTIVITIES OF THYMUS SATUREIOIDES COSS. ESSENTIAL OIL - Sbayou, Houda; Boumaza, Awatif; Hilali, Abderraouf; Amghar, Souad (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Thymus satureioides is a well-known aromatic perennial shrub widely used throughout the Mediterranean basin as a culinary herb, in traditional medicine for the treatment of a variety of diseases, and as a natural preservative ingredient in the food industry. The aim of this study was to analyze the chemical composition of T. Satureioides essential oil and to assess its antibacterial and antioxidant activities. Methods: The chemical composition of the essential oil was investigated by Gas chromatography-mass spectrometry (GC-MS). The essential oil was evaluated for its antibacterial activity against Gram-positive and Gram-negative bacteria using agar diffusion method and macro-broth dilution. The antioxidant activity was tested by three different methods, namely DPPH free radical scavenging, Î²-carotene/linoleic acid and TBARS assays. Results: Thirty compounds were identified, representing 85.52% of the total composition of this essential oil. Borneol (26.45%) and thymol (11.24%) were the major components. The oil had a bactericidal activity against all tested bacteria, with the exception of Pseudomonas aeruginosa. In addition, the T. satureioides essential oil revealed strong antioxidant activity in all conducted assays. Conclusion: The findings suggest that essential oil of T. satureioides may be used as an alternative to synthetic antibiotics and antioxidants.